Displacement and Resistance Strategies of the Pastoralists Afar in Ethiopia - Abeshu, Gemechu (Anthropologica)

(untitled) (University of Victoria, 2025)
This paper examines the resistance strategies of the displaced pastoralist Afar people in Northeast Ethiopia, focusing on the Lubakubo clan of the Dobi area. The Afar have historically practiced transhumant pastoralism, sustaining their livelihoods through the herding of livestock across arid and semi-arid landscapes. In 2004, a local “big man,” backed by the Ethiopian government and private investors, forcibly displaced members of the Lubakubo clan to facilitate commercial salt mining in Dobi, disrupting their socio-economic systems, cultural ties to the land, and traditional pastoral routes. Drawing on multi-sited ethnographic fieldwork conducted between 2015 and 2017, including in-depth interviews, participant observation, and archival research, this paper documents how the Afar mobilized lineage members, customary institutions, and strategic alliances to counter and contest the dispossession. These resistance strategies ranged from legal petitions and engagement with Afar traditional governance and conflict resolution structures to confrontation and symbolic acts reinforcing territorial claims. By situating these strategies within the broader political economy of resource extraction and displacement in the Horn of Africa, the paper contributes to scholarly debates on Indigenous resistance, land rights, and state–local power dynamics. The findings highlight the agency of displaced pastoralists in asserting their rights against state-backed commercial interests, while underscoring the resilience and adaptability of pastoralist systems under conditions of protracted displacement.